Investigation on musculoskeletal disorders among office workers in Putrajaya / Marlyza Said - Marlyza , Said (2019)
Majority of office workers are sedentary and generally work in sitting position for much of the day and it is common for office workers to sit for more than 30 minutes at a time. Due to the above routine and activities it may cause musculoskeletal stress on different body regions of seated workers and is a major factor in development of musculoskeletal disorders (MSDs). Therefore, the aim of the study is to identify level of MSDs risk and the prevalence MSDs among office workers and to observe the knowledge and behavior. A study was done among 60 workers by using questionnaire survey and Nordic Musculoskeletal Questionnaires (NMQ) and another 20 workers by using Rapid Upper Limb Assessment (RULA). Statistical analyses were performed using the Statistical Package for the Social Sciences software using Spearman Correlation and Chi-square tests. From the analysis, it was found that knowledge on proper posture demonstrated significant association with the MSDs symptoms (χ²=0.014) and were identified as one of the factors that lead to MSDs. The results of the NMQ revealed that that shoulder, upper back, lower back and neck were the most prevalent problems reported by office workers. Repetition, awkward postures or long-term static postures are considered the principal physical work-related risk factors in relation to MSDs. There is no relationship between gender, age, education level and frequency of exercise with the symptoms of MSDs. However, age was found to have a positive correlation with the MSDs symptoms. Finally, the RULA final score was 4 (low risk) indicating that further investigation is needed and change of posture may be required. The wrist and trunk are the most significant impact of body region at sitting position. As a conclusion, MSDs can be prevented by multidisciplinary approach. This study also provide recommendation to reduce the risk of MSDs. The study highlighted that there is a need to further improve the work design and introduce a control measure as to to heighten the working conditions ergonomically and finally improve the work productivity in general.